Informing climate-smart agriculture in low resource settings for practitioners: A review and analysis of interactive tools [version 1; peer review: 1 approved, 2 approved with reservations] - Kirsten Franzen; Daniel Lapidus; Tyler Ovington; Caleb Milliken; Jenny Frankel-Reed (Gates Open Research)
Background Agricultural producers in developing countries are uniquely vulnerable to the impacts of climate change and have the least ability to adapt. While there is a growing consensus that more financing and resources are needed to address these impacts, information on how to direct funding and support adaptation is dispersed and difficult to find. Agricultural development stakeholders and investors can leverage increasingly available data from a range of online sources to inform their climate smart agriculture investments, but it is not always clear which data tools are easily accessible and which can support different aspects of their programs. Methods This analysis aims to inform stakeholders how different tools can inform their climate smart investments. Hundreds of interactive tools were reviewed from multiple sources and a set of criteria was developed to simplify and elucidate the landscape of resources available that support adaptation and GHG mitigation for agricultural producers in low-income countries. The search strategy included a literature review, discussions with key stakeholders, and a review of existing databases of tools (e.g., NDC Partnership Toolbox). Results Ultimately 29 tools were identified and compared in terms of how they address both climate risk, adaptation, and mitigation. The data sources behind the tools were also compared, and illustrative user groups were identified. Many valuable, easy-to-use tools exist offering non-climate experts’ opportunities to gain insights into the relationship between climate and small-scale farming systems. However, the tools available are insufficient and should not be relied upon exclusively for informing investments. Conclusions This review provides a valuable resource for those looking to inform investments and programming in small-scale agriculture. This set of tools can provide insights that can be leveraged in various ways for a wide range of users, but they also have considerable limitations. This review can help users understand how these tools can be useful and the types of additional context-specific and local information that should be sought.